Cross-Linked Poly(cyclotriphosphazene-co-phloretin) Microspheres and Their Application for Controlled Drug Delivery - Mehmood, Sahid; Yu, Haojie; Wang, Li; Uddin, Md Alim; Amin, Bilal Ul; Haq, Fazal; Fahad, Shah; Haroon, Muhammad (Macromolecular research, 2022)
In this work, cross-linked poly(cyclotriphosphazene- co -phloretin) (PCTPPT) microspheres were synthesized and characterized by Fourier transform infrared (FT-IR) spectroscopy and scanning electron microscope (SEM). In FT-IR spectra, the new appeared bands at 1009 cm −1 and 1132 cm −1 confirmed the successful polymerization between hexachlorocyclotriphosphazene (HCCP) and phloretin (Pht). While the SEM results showed that the size of the microspheres was strongly dependent on the HCCP:Pht mole ratio. The crystalline nature of the PCTPPT microspheres was checked by X-ray diffraction (XRD) and provided evidence for the successful preparation of the microspheres. The thermal stability of the PCTPPT microspheres was investigated by thermogravimetric analysis (TGA). The obtained TGA results showed that the increase in thermal stability was attributed to the highly cross-linked covalently bonded structure of PCTPPT microspheres. The particle size distribution was determined by dynamic light scattering (DLS) and the results showed that the decreased HCCP:Pht mole ratio increases the size of the microspheres. The PCTPPT-3 microspheres were used as drug carriers for a model drug camptothecin (CPT). The experimental findings showed a cumulative release of 41.0% in pH 4.0 and 32.6% in pH 7.4 after 350 h and the PCTPPT-3/CPT microspheres have good drug loading capability and controlled release property for CPT.